2010
DOI: 10.1007/s00424-010-0880-7
|View full text |Cite
|
Sign up to set email alerts
|

CCK mediated the inhibitory effect of oxytocin on the contraction of longitudinal muscle strips of duodenum in male rats

Abstract: The aim of the present study was to investigate the effect of oxytocin (OT) on duodenum motility in rats and the possibility that cholecystokinin (CCK) was involved in this process. The isometric contraction of longitudinal muscle strips of duodenum was monitored by polygraph. ELISA was used to measure the concentration of CCK and OT in duodenum. CCK mRNA was assayed by RT-PCR. Oxytocin receptor (OTR) and CCK in duodenum were located by immunohistochemistry and immunofluorescence staining. OT (10⁻⁵ and 10⁻⁶ M)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 23 publications
3
19
0
Order By: Relevance
“…Oxytocin appears to reduce motility in isolated muscle strips (Xie et al. 2006; Lv et al. 2010), but for the intact colon it enhances peristalsis (Ohlsson et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxytocin appears to reduce motility in isolated muscle strips (Xie et al. 2006; Lv et al. 2010), but for the intact colon it enhances peristalsis (Ohlsson et al.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that OTR are expressed on myenteric neurons in rat duodenum, and that OT inhibits spontaneous neuronally dependent contractions of longitudinal muscle strips in vitro (Lv et al. 2010).…”
mentioning
confidence: 99%
“…Oxytocin receptor (OTR), a member of the G-proteincoupled receptor family, is distributed in the brain and peripheral tissues (Gimpl and Fahrenholz, 2001;Kimura et al, 2003;Lv et al, 2010;Viero et al, 2010;Boccia et al, 2013). It is known that the OTR is expressed in the dorsal root ganglia (DRG), principally in non-peptidergic C-fiber cell bodies (Moreno-Lopez et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This infection causes upregulation of CCK and 5-HT expression in EECs, both of which are implicated in hypophagia (Burton-Freeman et al, 1999; Hayes et al, 2006). Furthermore, CCK and IL-4 induce contractions in the longitudinal muscle (Lv et al, 2010; Zhao et al, 2003), and increased contractibility of the GI tract is associated with T. spiralis expulsion (Vallance et al, 1997). Interestingly, prior T. spiralis infection increases sensitivity of mouse enteric neurons to T. spiralis antigens, and this heightened sensitivity is abrogated by histamine receptor antagonism (Frieling et al, 1994).…”
Section: Introductionmentioning
confidence: 99%